2020
DOI: 10.1097/ogx.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Labor: An Overview of Guidelines

Abstract: Importance Induction of labor (IOL) is a common obstetric intervention that stimulates the onset of labor using artificial methods. Objective The aim of this study was to summarize and compare recommendations from 4 national or international medical societies on the IOL. Evidence Acquisition A descriptive review was conducted of major published guidelines on IOL: the American College of Obstetricians and Gyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
62
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 50 publications
1
62
0
2
Order By: Relevance
“…Based on previous findings, it has been suggested that more attention should be paid to low‐dose misoprostol for induction of labor. Vaginal doses of 25 µg every 3–6 h have been recommended only if the recipients can be kept under constant supervision 5–7 . The oral administration of misoprostol, on the other hand, is easier and has greater acceptability among women, when compared to vaginal administration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous findings, it has been suggested that more attention should be paid to low‐dose misoprostol for induction of labor. Vaginal doses of 25 µg every 3–6 h have been recommended only if the recipients can be kept under constant supervision 5–7 . The oral administration of misoprostol, on the other hand, is easier and has greater acceptability among women, when compared to vaginal administration.…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal doses of 25 µg every 3–6 h have been recommended only if the recipients can be kept under constant supervision. 5 , 6 , 7 The oral administration of misoprostol, on the other hand, is easier and has greater acceptability among women, when compared to vaginal administration. In 1996, Ngai et al 8 reported the use of oral misoprostol for pre‐labor rupture of membranes at term.…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended that the gestational age at delivery should be <42 weeks [2]. Women with low-risk pregnancies are advised to terminate the pregnancy between 41 and 42 weeks of gestation, suggesting that women at >41 weeks of gestation without spontaneous parturition should undergo IOL [3].…”
Section: Introductionmentioning
confidence: 99%
“…ο κίνδυνος ρήξης της μήτρας (3,4/1.000) ή διάσπασης της ουλής της καισαρικής τομής (2,6/1.000) ήταν μικρότερος στις περιπτώσεις ΠΤ(226). Επιπρόσθετα, το ΜΤ έχει αποδειχθεί ότι έχει υψηλή προγνωστική ικανότητα για την πρόβλεψη επιτυχούς κολπικού τοκετού μετά από καισαρική τομή (area under the curve -AUC: 0,76/ 95% CI: 0,663-0,856/ p<0,001)(227).Αξίζει να αναφερθεί ότι σε ορισμένες περιπτώσεις απαιτείται περάτωση της κύησης πρόωρα και αυτό επιτυγχάνεται συνήθως με πρόκληση τοκετού (εκτός αν υπάρχουν αντενδείξεις)(228). Τέτοιες περιπτώσεις αποτελούν η ΠΠΡΕΥ μετά τις 34 εβδομάδες της κύησης, η χοριοαμνιονίτιδα, η σοβαρή προεκλαμψία ή ενδομήτρια βραδύτητα της αύξησης του εμβρύου και ο εμβρυικός θάνατος(228).…”
unclassified
“…Επιπρόσθετα, το ΜΤ έχει αποδειχθεί ότι έχει υψηλή προγνωστική ικανότητα για την πρόβλεψη επιτυχούς κολπικού τοκετού μετά από καισαρική τομή (area under the curve -AUC: 0,76/ 95% CI: 0,663-0,856/ p<0,001)(227).Αξίζει να αναφερθεί ότι σε ορισμένες περιπτώσεις απαιτείται περάτωση της κύησης πρόωρα και αυτό επιτυγχάνεται συνήθως με πρόκληση τοκετού (εκτός αν υπάρχουν αντενδείξεις)(228). Τέτοιες περιπτώσεις αποτελούν η ΠΠΡΕΥ μετά τις 34 εβδομάδες της κύησης, η χοριοαμνιονίτιδα, η σοβαρή προεκλαμψία ή ενδομήτρια βραδύτητα της αύξησης του εμβρύου και ο εμβρυικός θάνατος(228). Το ΜΤ φαίνεται ότι και εδώ έχει σημασία, μιας και σε μια μελέτη 475 εγκύων που υποβλήθηκαν σε πρόκληση τοκετού βρέθηκε ότι το ΜΤ αποτέλεσε ανεξάρτητο προγνωστικό παράγοντα πρόβλεψης της καισαρικής τομής (aOR: 1,717/ 95% CI: 1,077-1,663) (229).2.1.7 ΠρόληψηΟι στρατηγικές πρόληψης του ΠΤ διακρίνονται στην πρωτογενή (όταν εφαρμόζεται στον γενικό πληθυσμό), τη δευτερογενή (όταν εφαρμόζεται σε πληθυσμό υψηλού κινδύνου) βραδύτητας της αύξησης(161).…”
unclassified